Midwives' Evaluation of a Neonatal Resuscitation in High- and Low-Resource Settings - Cavallin, Francesco; Calgaro, Serena; Borellini, Martina; Magnani, Margherita; Beltramini, Greta; Seni, Amir Hussein Abubacar; Cebola, Bonifacio Rodriguez; Tambo, Ana Nicolau; Putoto, Giovanni; Trevisanuto, Daniele (Frontiers in Pediatrics, 2021)
Aim: To assess midwives’ evaluation of a real-life neonatal resuscitation and their opinion on importance of resuscitation interventions. Methods: Multicenter, multi-country study. Setting: Beira Central Hospital (Mozambique) and Azienda Ospedale-Università di Padova (Italy). Subjects: 16 Mozambican midwives and 18 Italian midwives. Interventions: Midwives’ assessment was evaluated by using a predefined score, which graded each resuscitation intervention (0-2 points) and summed to a total score for each step (initial steps, bag-mask ventilation and chest compressions). All scores were compared with referral scores given by two expert neonatologists. Results: Both Mozambican and Italian midwives overestimated their performance regarding of initial steps taken during resuscitation, chest compressions, high-oxygen concentrations (p<0.01), and underestimated the importance of stimulation (p<0.05). Mozambicans overestimated suctioning (p<0.001). Participants agreed with experts about the importance of equipment preparation, using a warmer, drying the newborn, removing wet linen and heart rate assessment. Conclusion: Mozambican and Italian midwives overestimated the performance of a real-life neonatal resuscitation, with heterogeneous evaluation of the importance of several aspects of neonatal resuscitation. These findings may be useful for identifying educational goals.